PENGARUH PEMBELAJARAN DI RUANG TERBUKA HIJAU TERHADAP MOTIVASI BELAJAR SISWA - Fiki Zida Farhana (Jurnal Tata Kelola Pendidikan, 2021)
The development of facilities and infrastructure that is increasingly being carried out in urban  areas and the rapid growth of population causes limited green open space. Green open space itself has many benefits if its existence is cared for and managed well. Green open spaces are also being intensely procured in cities, provinces and schools. It is known that if a green open space is provided at school it can be one of the learning resources that can optimize learning achievement. Because unwittingly green open space which contains a place to grow plants with a green color that can reduce boredom when students feel monotonous learning activities. So it is hoped that the opening of green open land in schools as a source of learning can increase student motivation and can improve student’s critical thinking processes about everyday phenomena.